2H2S+3O2=2SO2+2H2O
S -2 -6e=S +4 |4|2
O2 0 +4e=O2 2- |6|3
H2(с.о.+1)S(с.о.-2)+O2(с.о.0)=S(с.о.+4)O2(с.о.-2)+H2(с.о.+1)O(с.о.-2)
заметка: с.о.- это степень окисления
S(с.о.-2)-6 электронов=S(с.о.+4)|4 |2 S(с.о. -2)-восстановитель
O2(с.о. 0)+4 электрона=2O(с.о.-2)| 6 |3 O2(с.о. 0)-окислитель
значит уравнение будет выглядеть так:
2H2S+3O2=2SO2+2H2O
S -2 -6e=S +4 |4|2
O2 0 +4e=O2 2- |6|3
H2(с.о.+1)S(с.о.-2)+O2(с.о.0)=S(с.о.+4)O2(с.о.-2)+H2(с.о.+1)O(с.о.-2)
заметка: с.о.- это степень окисления
S(с.о.-2)-6 электронов=S(с.о.+4)|4 |2 S(с.о. -2)-восстановитель
O2(с.о. 0)+4 электрона=2O(с.о.-2)| 6 |3 O2(с.о. 0)-окислитель
значит уравнение будет выглядеть так:
2H2S+3O2=2SO2+2H2O